The Urgency of Religious Institutions in the Middle of the Localization Complex in Bandung - Solihin, Solihin; Bukhori, Bukhori (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2022)
This study describes the community's efforts to stem harmful activities by promoting positive activities, namely, establishing Islamic boarding schools in the Saritem environment as a place of localization in the city of Bandung. The method used in this research is descriptive with a qualitative approach. Observations, interviews, and documentation are part of the data collection process in this study. This study adopts the idea of adaptation proposed by Talcott Parsons with the theory of AGIL (Adaptation, Goal Attainment, Integration, Latency). So, we get three research results that describe the adaptation of Islamic boarding school teachings to prostitutes in the localization environment, namely the existence of cultural and religious life of the community, the existence of an open consultation place to improve and foster community behavior, and the existence of good relations with the community. This study reaffirms the social function of religious institutions so that community activities become balanced and healthy, both physically and spiritually.